ENDOSCOPIC ULTRASOUND IN THE EVALUATION OF UPPER SUBEPITHELIAL LESIONS - CHAVES,Dalton Marques (2015)
BackgroundEndoscopic ultrasound is considered the best imaging test for the diagnosis and evaluation of subepithelial lesions of the gastrointestinal tract.ObjectiveThe present study aims to describe the endosonographic characteristics of upper gastric subepithelial lesions and our experience using endoscopic ultrasound for evaluation of such lesions.MethodsRetrospective data study of 342 patients who underwent endoscopic ultrasound evaluation of subepithelial lesions.ResultsLesions of the fourth layer were more common in the stomach (63.72%) than in the esophagus (44.68%) and duodenum (29.03%). In stomach, 81.1% of the lesions ≥2 cm, and 96.5% ≥3 cm, were from the fourth layer. Endosonographic signs that could be related to malignant behavior, such as irregular borders, echogenic foci, cystic spaces and/or size greater than 3 cm were identified in 34 (15.81%) lesions at the first endoscopic ultrasound evaluation. Endoscopic ultrasound-fine needle aspiration did the diagnosis in 21 (61.76%) patients who were submitted a puncture. Three (12.0%) lesions of 25 who were submitted to regular endoscopic ultrasound surveillance increased the size.ConclusionStomach is the organ most affected with subepithelial lesions of the gastrointestinal tract and the fourth layer was the most common layer of origin. More than 80% of gastric subepithelial lesions from the fourth layer are ≥2 cm. Endoscopic ultrasound evaluation of subepithelial lesions has been very important for stratification into risk groups and to determine the best management.